Comparative analysis of service characteristics of transportation network companies (TNCs) and conventional taxis - Paronda, Arden Glenn A.
This study presents the characteristics of TNC users and operators: perception of commuters and operators on Uber and GrabCar; the role of Uber and GrabCar in our transportation sector and sustainable tran sport in Metro Manila; and recommendations for TNCs as well as for improving conventional taxi services. This research also presents a comparative analysis of Key Performance Indicators (KPI) of TNCs vs. Conventional Taxis. The Key Performance Indicators include travel speed, reliability, passenger expense, and quality of service. Travel diaries from regular riders of Uber, GrabCar and Conventional Taxis ran for 30 days in order to gather data and compare its KPls. Hence, surveys such as: (I) availability of vehicle check and (2) performance indicator survey were also conducted in order to validate and support the travel diaries submitted by the regular riders. The rise of the TNC transport modes proved that there are problems in the current conventional taxi service in Metro Manila. Overcharging, Reckless Driving, Rude Driver are found to be the most common complaints people experience in riding a taxi in Metro Manila. From the survey conducted, it was found out that 62% of Uber and GrabCar users are also private car owners. It is noted that 57% are female and 47% of the users have a Bachelor's Degree. Hence, 76% of riders are anticipated to be employed. Furthermore, it is noted that the average age of Uber and GrabCar users is 31.48 years old, and the median is at 30 years old. The study determined that due to the poor public transport system, most numbers of women opt to ride either a conventional taxi or book a ride through Uber or GrabCar for safety and convenience. Hence, Convenience, Safety, Reliability, Less hassle, Just like my own car, Easy to book a ride, Cashless Payment, Drivers have undergone background check, and Cars are new are the top reasons why people book a ride through Uber and GrabCar. Moreover, 57% of the respondents are willing to give up their car for a convenient mode of transportation. The other 43%, however still prefer to have a car because of the present condition of our transportation sector as evident in the growing sales of cars. The primary purpose of riding Uber and GrabCar of the respondents is to "commute to work" . 24% of the respondents are willing to add 100 to 150 pesos for a convenient and reliable ride. Based from the results of the travel diary submitted, Uber is faster than GrabCar and Conventional Taxi with 21 .32 kilometers per hour (kph). In terms of reliability or the number of available vehicles at a specified pick lip point, GrabCar dominates the number of vehicles available than Uber and Conventional Taxi with the highest value of 7.6. Uber is said to be cheaper than conventional taxis with a rate of Php 20.72 per kilometer. However, GrabCar is costlier at a rate of PhP 32.07 per kilometer. Lastly, Uber and GrabCar has better quality of service compared to conventional taxis with the highest rating of 4.82. The average age of the Uber or GrabCar Operators who answered the survey is 35.8 years old with a median of 35. Mixed ages ranging from 20 to 60 years old are observed. 60% of the respondents are Uber operators, 25% are GrabCar operators and the remaining 15% are both Uber and GrabCar operators. The average number of units the operator has is at 1.36 units with a median of 1.0. Most of the respondent operators came from different fields of work before Uber and GrabCar arise. 52% are both driver and operator, 33% are solely operators, while 15% are only drivers. The top reason why the operators joined Uber or GrabCar is to have an additional income. Based on the online survey conducted, Uber and GrabCar operators work at an average of 5.35 times a week, at 11 to 12 hours a day or even at 16 hours and 70% of operators bought their vehicle brand new. The reasons on how TNCs like Uber and GrabCar can contribute to sustainable transport are as follows: a) If it supplements to urban public transit rather than a substitute for it; b) When ride-sharing principle is applied; c) When competition with taxi service benefits the consumerS; d) By promoting safety; e) Through the lise of Intelligent Transport System (ITS) and In formation Communication Technologies (ICT). While the reasons why TNCs does not contribute to sustainable transport are as follows: a) If Uber and GrabCar service is not available, the 44% of the riders will shift to tax i. while 32% will use public transportation; b) If Uber and GrabCar service is stopped, the 29% of the riders will use the transit more often, 24% will use tax is more often, and 15% will walk more often: c) 70% of the operators bought their vehicle brand new for Uber or GrabCar; d) Most of the operators of Uber and GrabCar works 6 times a week and at 11 to 12 hours a day and some are even at 16 hours a day. Analysis show that TNCs, particularly Uber and GrabCar, do not help in contributing to a sustainable transport system. Furthermore, dispatching method like Global Positioning System (GPS) and radio communication should be used based on demand of passengers per city and per time in taxis. Further studies should be undertaken regarding fare setting and the maximum age of vehicle for TNCs. TNCs like Uber and GrabCar should find ways to minimize driver trip rejection of passengers and sanctions can be imposed to picky drivers. Other TNCs should immediately process the accreditation with LTFRB to legalize its operation. Trade dress with branding logo requirement should be enforced to TNC vehicles to associate to its operator. TNCs should not perform as a rent a car se rvice or through hailing. A trip request shall only be done through online booking via TNC Application. TNCs should comply with all the other requirements mandated by the Government and should be regulated to ensure the safety of the public. The number of vehicles per operator should be limited to give chance to other private car owners to rideshare through TNC. In order to contribute to a sustainable transport, TNCs should consider the concept of ride-sharing by maximizing the occupancy of the vehicle, and by encouraging the people to share their ride. TNCs should highly di scourage its members to buy new vehicles but instead utilize the existing units in good condition and qualified to the age requirement set by LTFRB.